KARAKTERISTIK SIFAT FISIK TANAH ULTISOL BERDASARKAN TINGKAT KEMIRINGAN LERENG - Eko Dedi Septiaji; John Bimasri; Zaini Amin (Agroteknologi Fakultas Pertanian Universitas Islam Darul 'Ulum (UNISDA), 2024)
Ultisol soil has slow permeability and low aggregate stability, so it has low water holding capacity and is sensitive to erosion. The research was carried out from January to February 2024, in the Kebon Kito Agrotourism area at coordinates 3O19'20.52